A bibliometric and systematic review of case-based learning research on critical thinking in preservice teachers - Etika Khaerunnisa; Heni Pujiastuti; Cecep Anwar Hadi Firdos Santosa (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: The growing emphasis on higher-order thinking skills has positioned case-based learning (CBL) as a prominent pedagogical approach in contemporary education. Although prior studies highlight its potential to enhance critical thinking, research trends and thematic focus particularly involving preservice teachers remain insufficiently synthesized. Aims: This study aims to identify research trends, bibliometric characteristics, and gaps related to the effectiveness of CBL in improving critical thinking skills, with a specific focus on preservice teachers. The scope includes Scopus-indexed publications from 2015 to 2025. The use of Scopus is considered by taking into account several factors, including quality assurance standards (peer-reviewed publications), reputation and credibility indicators (Scimago Journal Rank/SJR), and its broad multidisciplinary coverage. However, certain limitations remain, such as publication bias related to language and geographical representation, the presence of grey literature, and bias associated with publication types. Methods: A Systematic Literature Review (SLR) combined with bibliometric analysis was conducted. Articles were selected based on predefined inclusion criteria and analyzed by country, subject area, journal quartile, SJR, and H-index. Keyword co-occurrence mapping was performed using VOSviewer. Results: A total of 86 articles met the inclusion criteria, predominantly published in Q1 and Q2 journals within the Social Sciences domain. Bibliometric visualization shows that CBL and critical thinking are widely explored topics; however, studies focusing on preservice teachers and their relationship with decision making (CBL and critical thinking) remain limited. Conclusion: The findings indicate strong scholarly interest in CBL while revealing a clear research gap concerning preservice teachers populations. Future research should prioritize the development of standardized instruments and expand empirical investigations to strengthen evidence-based practices in teacher education.